Effect of Cd1-xMnxSe Alloy Thickness on the Optical and Photovoltaic Properties of Quantum Dot-Sensitized Solar Cells - Tung, Ha Thanh; Phuc, Dang Huu (Frontiers in Materials, 2019)
In this work, the Cd1-xMnxSe alloy was successfully prepared using successive ionic layer adsorption and reaction method to investigate the layers effect on the properties of devices while concentration dopant was optimized at 20% (molar concentrations between Mn2+ and Cd2+ ions in the Cd1-xMnxSe material). The layers of the Cd1-xMnxSe alloy play a role in the improving optical, photovoltaic and electrochemical properties of the solar cells. Hence, the efficiency performance of devices based on the Cd1-xMnxSe alloy reached approximately 3.8%. Besides, in order to explain this result, the experimental I-V curve was also used to determine the resistances at the interfaces and the resistances diffusion of the devices. This dynamic resistance can be compared with that of Electrochemical Impedance Spectra.